2016
DOI: 10.1371/journal.pone.0167462
|View full text |Cite
|
Sign up to set email alerts
|

Food-Induced Emotional Resonance Improves Emotion Recognition

Abstract: The effect of food substances on emotional states has been widely investigated, showing, for example, that eating chocolate is able to reduce negative mood. Here, for the first time, we have shown that the consumption of specific food substances is not only able to induce particular emotional states, but more importantly, to facilitate recognition of corresponding emotional facial expressions in others. Participants were asked to perform an emotion recognition task before and after eating either a piece of cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…However, none of these studies explored the synergetic effect of combining tDCS to the PFC with CBM designed to train avoidance to chocolate stimuli. Chocolate is one of the most craved foods in western countries (Meule and Hormes, 2015; Richard et al, 2017), because its high energy density and its association with pleasant emotions (Pandolfi et al, 2016). Moreover, past studies have not combined CBM with tDCS in order to maximize the effects on food craving reduction of each other, nor have been using implicit measures for assessing the effects of such interventions on food craving.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these studies explored the synergetic effect of combining tDCS to the PFC with CBM designed to train avoidance to chocolate stimuli. Chocolate is one of the most craved foods in western countries (Meule and Hormes, 2015; Richard et al, 2017), because its high energy density and its association with pleasant emotions (Pandolfi et al, 2016). Moreover, past studies have not combined CBM with tDCS in order to maximize the effects on food craving reduction of each other, nor have been using implicit measures for assessing the effects of such interventions on food craving.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, offering dark chocolate is something that can be easily done in many service settings, does not require a specific skills-set of your employees, and has a rather limited cost. Furthermore, as dark chocolate works fast (Pandolfi et al, 2016), is (perceived as) relatively healthy (Tuenter et al, 2018), yet highly hedonic, it makes an ideal small detail to give to your customers.…”
Section: Theoretical and Managerial Contributionsmentioning
confidence: 99%
“…The present paper investigates whether offering a small piece of dark chocolate for immediate consumption (small detail) at the beginning of a service experience improves customers' performance outcomes. The focus lies on offering dark chocolate because layman beliefs and academic literature, suggest that eating dark chocolate even in small amounts elevates mood (Macht and Dettmer, 2006;Pandolfi et al, 2016). In addition, offering dark chocolate is something that many service providers can easily do with limited costs.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the consumption of chocolate could diminish negative mood while “happy” and “surprise” emotions were frequently related with a sweet taste [ 29 ]. In our previous study, food-elicited emotions were measured using facial expression recognition software and results showed that the milk chocolate had the highest intensity of emotion “happy”, and reduced the level of the neutral state [ 30 ].…”
Section: Introductionmentioning
confidence: 99%